Inhibition of the Metastasis of Lewis Lung Carcinoma by Antibody Against Urokinase-Type Plasminogen Activator in the Experimental and Spontaneous Metastasis Model - Kobayashi, Hiroshi; Gotoh, Junko; Shinohara, Hiromitsu; Moniwa, Nobuhiko; Terao, Toshihiko (Thrombosis and Haemostasis, 1994)
A selective inhibitory antibody, raised against human high molecular weight urokinase-type plasminogen activator (HMW-uPA), was examined to determine whether it would inhibit production of experimental and spontaneous lung metastasis by murine Lewis lung carcinoma (3LL) cells. Polyclonal antibody to human uPA cross-reads with the murine uPA and inhibits murine uPA activity. When examined with an in vitro assay system using a modified Boyden chamber, the anti-catalytic IgG to uPA suppressed the invasion of tumor cells through Matrigel. Anti-uPA IgG inhibited neither the cell proliferation nor the binding of tumor cells to Matrigel, and showed no significant suppression of chemotactic migration of tumor cells to tibronectin. In an in vivo spontaneous metastasis assay, multiple subcutaneous (s. c.) injections of anti-uPA IgG (up to a concentration of 200 pg [ 500 inhibitory unit/mousc/day]) for 7 days immediately after s. c. tumor cell inoculation significantly inhibited the formation of lung metastasis in C57BL/6 mice in a dose-dependent manner. The inhibition of lung metastasis was not due to direct antitumor effects of anti-uPA IgG. In an in vivo experimental metastasis assay, multiple s. c. injections of anti-uPA IgG for 7 days after intravenous (i. v.) tumor cell inoculation did not reduce the number of lung tumor colonies. These results suggest that uPA more efficiently regulates the mechanism involved in the entry into vascular circulation of tumor cells (intravasation) than in extravasation, during the metastatic process.